What’s biodiversity got to do with it? Perceptions of biodiversity and restorativeness in urban parks - Gonçalves, Paula (2022)
Understanding the mechanisms underlying the positive influence of urban biodiversity on dwellers’ well-being is critical to inform sustainable management of urban greenspaces, but studies published to date on the role of biodiversity in mental restoration have provided contradictory results. Both urban greenspace biophysical characteristics and the emotional connection with the place may play a role in mental restoration. Using urban greenspace landscape and biodiversity metrics, and on-site observations and questionnaires to assess site quality and visitors’ perceptions, we explore the influence of biodiversity (perceived and measured at different levels), urban greenspace characteristics, and visitors profiles in mental restoration. Our statistical analysis demonstrates that perception of biodiversity, along with satisfaction and connection to place, were the most important predictors of mental restoration. The proportion of broadleaf and evergreen tree species also had a positive influence on biodiversity perception and mental restoration. People perceive existing biodiversity through visual cues as the diversity of leaf forms in broadleaf species, with this process being almost completely mediated by the perception of tree diversity. These findings have direct translation into planning and management practices by acknowledging the importance of biodiversity and, above all, specific traits, namely of evergreen broadleaf species, in promoting restorativeness of urban parks for users. Our results highlight the importance of using standard ecological methods when assessing biodiversity in urban greenspaces and their influence on human well-being.